THE PRIORITY NEEDS FOR DEVELOPING SECONDARY SCHOOL ACADEMIC MANAGEMENT BASED ON THE CONCEPT OF FREEDOM WITH RESPONSIBILITY - Puranasamriddhi, Achimawan; Siribanpitak, Pruet; Xupravati, Penvara (Journal of MCU Nakhondhat, 2025)
This research aims to analyze the needs for academic administration in secondary schools based on the concept of freedom with responsibility. A mixed-methods research design was employed, combining both quantitative and qualitative approaches. The sample consisted of 342 secondary schools under 62 Secondary Educational Service Area Offices nationwide. The primary research instrument used to collect data was a structured questionnaire utilizing a five-point Likert scale. Data analysis was conducted using descriptive statistics, including frequency distribution, percentage, mean, standard deviation, and calculation of the Modified Priority Needs Index (PNImodified) to determine the gap between the current and desired states. The results of the study revealed that the area with the highest priority needs in academic management based on the concept of freedom with responsibility was measurement and evaluation (PNI Modified = 0.122). This was followed by instructional media development (PNI Modified = 0.114), co-curricular activity implementation (PNI Modified = 0.106), curriculum development (PNI Modified = 0.096), and instructional management (PNI Modified = 0.066), respectively. These results suggest areas where schools need targeted improvement aligned with the concept of reponible freedom. Furthermore, when considering the dimension of freedom with responsibility, the highest priority was freedom of expression, speech with responsibility to listen (PNI Modified = 0.108), followed by freedom of worship with responsibility to accept (PNI Modified = 0.107), freedom from fear with responsibility to act (PNI Modified = 0.095), and the lowest need was found in the area of freedom from want with responsibility to serve (PNI Modified = 0.092). These findings reflect the diverse perspectives and needs regarding the development of academic administration in secondary schools, emphasizing the importance of integrating the principle of freedom with responsibility into educational leadership and policy frameworks.